Utilization of Biopertalite for Fuel Efficiency and Reduction in CO and CO2 Gas Emissions in Four-Wheel Motor Vehicles - Iskandar, Ridwan; Hadiyanto, Hadiyanto; Suherman, Suherman; Zakaria, Zainul Akmar (Makara Journal of Technology, 2022)
Emissions of carbon monoxide (CO) and carbon dioxide (CO2) gases are the main problem that must be rectified as they are harmful and contribute to global warming through the greenhouse gas effect. In Indonesia, motor vehicles, especially four wheelers, are one of the biggest contributors with up to 71 million tons of CO2 emissions and energy consumption of 179 million barrel of oil equivalent. Bioethanol has octane rating >100, which is higher than that of gasoline; and emission contribution of only 0.02 kg/L, which is lower than that from gasoline (2.23 kg/L). Accordingly, a mixture of gasoline and bioethanol is the solution proposed in this study to solve the issues of CO and CO2 emissions. Gasoline and bioethanol mixture consists of six products, namely E-0, E-5, E-10, E-15, E-20, and E-25, which have different percentage values of bioethanol mixture (0%–25%). This study was conducted through engine testing with different rpm values (500–2500 rpm) to identify the concentration and mass of CO2 emissions, fuel efficiency, and cost efficiency. Based on the test results, this product succeeded in reducing CO emissions by up to 86% and CO2 emissions up to 30.6% from Pertalite (E-0) and increasing the fuel efficiency up to 51.76% for 1 L and cost efficiency up to 33.6% after considering the actual price of Pertalite. Therefore, the proposed product can be a solution to the existing problems.